THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND PRINCIPAL MANAGERIAL COMPETENCE TOWARDS TEACHERS’ PERFORMANCE - Wulandari, Yeni; Lian, Bukman; arafat, Yasir
This study aimed at determining the effect of transformational leadership and principal managerial competence towards teachers’ performance at SD Negeri Ilir Timur II Palembang. The data in this study were collected through the distribution of questionnaires on the respondents. The results of questionnaires were analyzed by using multiple regression analysis through ttest, Ftest, and coefficient of determination test. The population in this study is all primary teachers from 20 SD Negeri in Ilir Timur II Palembang which consist of 405 teachers. The sample size of the population in this study is based on calculations using the Slovin formula and the sampling technique used is the convenience sampling technique. So, the sample in this study were 80 (eighty) respondents. The results showed that (1) transformational leadership partially have a positive and significant effect on teachers’ performance; (2) partial managerial competence has a positive and significant effect on teachers’ performance; and (3) transformational leadership and managerial competencies simultaneously affect teachers’ performance.